2018
DOI: 10.1038/s41598-018-31553-9
|View full text |Cite
|
Sign up to set email alerts
|

Combining Bulk Temperature and Nanoheating Enables Advanced Magnetic Fluid Hyperthermia Efficacy on Pancreatic Tumor Cells

Abstract: Many efforts are made worldwide to establish magnetic fluid hyperthermia (MFH) as a treatment for organ-confined tumors. However, translation to clinical application hardly succeeds as it still lacks of understanding the mechanisms determining MFH cytotoxic effects. Here, we investigate the intracellular MFH efficacy with respect to different parameters and assess the intracellular cytotoxic effects in detail. For this, MiaPaCa-2 human pancreatic tumor cells and L929 murine fibroblasts were loaded with iron-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 56 publications
2
43
0
2
Order By: Relevance
“…As a result of these three mechanisms, SPION and magnetic temperature gradually increase in an AFM until a saturation temperature is achieved [37,38]. In a cellular environment, however, SPION are immobilized inside lysosomes and form agglomerates [39,40]. This leads to partial blocking of the above-mentioned Brownian relaxation and to a drop in heating efficiency.…”
Section: Magnetic Fluid Hyperthermiamentioning
confidence: 99%
“…As a result of these three mechanisms, SPION and magnetic temperature gradually increase in an AFM until a saturation temperature is achieved [37,38]. In a cellular environment, however, SPION are immobilized inside lysosomes and form agglomerates [39,40]. This leads to partial blocking of the above-mentioned Brownian relaxation and to a drop in heating efficiency.…”
Section: Magnetic Fluid Hyperthermiamentioning
confidence: 99%
“…The IT administration of MNPs seems to be generally considered a more invasive procedure than the IV counterpart and it is known to result in uneven distribution of the MNPs in the tumor, which can lead to a significant temperature difference across the tumor [ 76 ]. This can be minimized by multiple site IT injection [ 77 ] or by magnetic targeting of MNPs after IV injection, i.e., using an external magnet to concentrate the MNPs in the area of interest [ 76 , 78 ]. Magnetic targeting, combined with antibody targeting and the EPR effect, have been reported to allow the tumor to be specifically heated [ 60 ].…”
Section: Main Parameters Influencing the Outcome Of A Preclinical mentioning
confidence: 99%
“…Magnetic targeting, combined with antibody targeting and the EPR effect, have been reported to allow the tumor to be specifically heated [ 60 ]. Among the advantages of IT administration of MNPs are the less complex formulation usually required and that, in general, it results more effectively than the IV route [ 78 ]. Additionally, it opens the possibility to treat tumors where MNPs do not accumulate to sufficient amounts after IV injection.…”
Section: Main Parameters Influencing the Outcome Of A Preclinical mentioning
confidence: 99%
“…In addition to the abovementioned investigations, research studies from the last couple of years showed that NiCu MNPs have great potential in several other types of biomedical applications, such as their use in bimodal cancer treatments that combine MH and controlled drug delivery [47][48][49]. Nevertheless, another important factor to be considered when applying a novel formulation for MH is the overall concentration of the respective NPs at the tumor site [50,51]. Specifically, NPs with a low specific loss power (SLP) need to be more concentrated in the tumor, with the consequent disadvantages of bioaccumulation and long-term toxicity [52,53].…”
Section: Figurementioning
confidence: 99%